Realizing utopia the future of international law - Cassese, Antonio (Oxford : Oxford University Press, 2012)
Bringing together 47 essays by prominent international lawyers this book reflects on major challenges facing international law and focuses on potential changes and improvements. Its aim is helping to construct a better architecture of world society. As international law's importance continues to grow, this book analyses where it is heading.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International law